BENTUK MORFOLOGI KAWASAN PERMUKIMAN URBAN FRINGE SELATAN KOTA SURAKARTA - Mentari Adhika Putri; Murtanti Jani Rahayu; Rufia Adisetyana Putri (Diponegoro University, 2016)
Needs land settlement increasingly over the development of cities. Demands of land use settlement that can’t be accommodated by the city space to inflict urban sprawl to the urban fringe. Urban fringe development caused visibility of the morphology. Propose of the research is to know the form of morphology settlement urban fringe the southern Surakarta. This research used morphology form’s two step: (1) identified component in the form of morphology consisting of land use, road pattern, and the pattern building and (2) analyzed form of morphology settlement urban fringe the southern Surakarta with integrated the result of first step’s research. This research result show land use has mixed use, spinal road pattern, and diversity building pattern. It shows the form of morphology octopus.